2010
DOI: 10.1093/nar/gkq692
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the bacterial transcription-repair coupling factor/RNA polymerase interaction

Abstract: The transcription-repair coupling factor (TRCF, the product of the mfd gene) is a widely conserved bacterial protein that mediates transcription-coupled DNA repair. TRCF uses its ATP-dependent DNA translocase activity to remove transcription complexes stalled at sites of DNA damage, and stimulates repair by recruiting components of the nucleotide excision repair pathway to the site. A protein/protein interaction between TRCF and the β-subunit of RNA polymerase (RNAP) is essential for TRCF function. CarD (also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 47 publications
9
85
0
Order By: Relevance
“…The N terminus of the CarD protein displays amino acid sequence similarity to that of the RNAP interaction domain (RID) of the TRCF (the product of the mfd gene). We previously reported that Thermus thermophilus CarD interacts with the same region at the N terminus of the RNAP ␤ subunit (the ␤1 domain) as the T. thermophilus TRCF (22,24). Studies of Myxococcus xanthus proteins have reported similar findings (10).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The N terminus of the CarD protein displays amino acid sequence similarity to that of the RNAP interaction domain (RID) of the TRCF (the product of the mfd gene). We previously reported that Thermus thermophilus CarD interacts with the same region at the N terminus of the RNAP ␤ subunit (the ␤1 domain) as the T. thermophilus TRCF (22,24). Studies of Myxococcus xanthus proteins have reported similar findings (10).…”
Section: Resultsmentioning
confidence: 76%
“…The X-ray crystal structure of the T. thermophilus TRCF RID complexed with the Thermus aquaticus RNAP ␤1 domain (24) revealed that T. thermophilus TRCF RID R341 forms a hydrogen bond with RNAP ␤1 Q99, as well as polar interactions with RNAP ␤1 E110. The RNAP ␤1 residues I108 and K109 are also central to the protein/protein interface, making extensive van der Waals contacts with the TRCF RID (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7C) and, consequently, the dynamic equilibrium of TRCF conformations. Thus, the robust TEC release activity of oxidized TRCF-D2:D7, which is greatly impaired in DNA binding, suggests that the initial recognition of a stalled TEC is likely provided through specific protein-protein contacts between the RID and the β-subunit of RNAP (5,18,35) and that protein-DNA contacts play a secondary role.…”
Section: Nucleotide Binding and Hydrolysis Reorganize Interdomain Conmentioning
confidence: 99%
“…UvrC then nicks the DNA on either side of the lesion and the UvrD helicase removes the oligonucleotide, allowing the DNA Polymerase I to "re-synthesize" a new DNA using the complementary strand of DNA as template. [7][8][9][10][11][12][13] To complete the repair process, the LigA ligase joins the newly synthesized DNA to the adjacent pre-existing strand (Fig. 1).…”
Section: Mfd As a Central Partner Of Transcription Coupled Repairmentioning
confidence: 99%